Environmental tests of embedded thin‐ and thick‐film resistors in comparison to chip resistors. Issue 1 (2014) - ,; ,; ,; ,; ,
Abstract : Purpose – The purpose of this paper is to investigate the influence of parameters of embedded resistive elements manufacturing process as well as the influence of environmental factors on their electrical resistance. The investigations were made in comparison to the similar constructions of discrete chip resistors assembled to standard printed circuit boards (PCBs).Design/methodology/approach – The investigations were based on the thin‐film resistors made of NiP alloy, thick‐film resistors made of carbon or carbon‐silver inks as well as chip resistors in 0402 and 0603 packages. The polymer thick‐film resistive films were screen‐printed on the several types finishing materials of contact terminations such as copper, silver, and gold. To determine the sensitivity of embedded resistors versus standard assembled chip resistors on environmental exposure, the climatic chamber was used. The measurements of resistance were carried out periodically during the tests, and after the exposure cycles.Findings – The results show that the change of electrical resistance of embedded resistors, in dependence of construction and base material, is different and mainly not exceed the range of 3 per cent. The achieved results in reference to thin‐film resistors are comparable with results for standard chip resistors. However, the results that were obtained for thick‐film resistors with Ag and Ni/Au contacts are similar. It was not found the big differences between resistors with and without conformal coating.Research limitations/implications – The studies show that embedded resistors can be used interchangeably with chip resistors. It allows to save the area on the surface of PCB, occupied by these passive elements, for assembly of active elements (ICs) and thus enable to miniaturization of electronic devices. But embedding of passive elements into PCB requires to tackle the effect of each forming process steps on the operational properties.Originality/value – The technique of passive elements embedding into PCB is generally known; however, there are no detailed reports on the impact of individual process steps and environmental conditions on the stability of their electrical resistance. The studies allow to understand the importance of each factor process and the mechanisms of operational properties changes depending on the used materials. Acknowledgements : This work was supported by the National Science Center (Poland) Grant DEC‐2011/01/D/ST8/07155 (integration of passive elements with multilayer printed circuit board).